2010
DOI: 10.1002/marc.201000521
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Induced Polymer Degradation During Ink‐Jet Printing

Abstract: We report for the first time evidence of flow-induced polymer degradation during inkjet printing for both poly(methyl methacrylate) (PMMA) and polystyrene (PS) in good solvent. This has significance for the deposition of functional and biological materials. Polymers having Mw either less than 100 kDa or greater than approximately 1,000 kDa show no evidence of molecular weight degradation. The lower boundary condition is a consequence of low Deborah Number De imposed by the printhead geometry and the upper boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…We have used an average extension rate here rather than a local value, and the emerging jet tip speed is 2-3 times higher than the final drop speed. However, the agreement between the scaling predictions of the model and the experimental data from de and A-Alamry et al (2011), including both transitions, and with the trend of the experimental data from the present work within regime III, suggest that the model is well-founded. Morrison and Harlen (2010) reported numerical simulations of the jetting of viscoelastic fluids which also showed the same scaling law as that predicted for regime III.…”
Section: B Further Commentssupporting
confidence: 66%
See 1 more Smart Citation
“…We have used an average extension rate here rather than a local value, and the emerging jet tip speed is 2-3 times higher than the final drop speed. However, the agreement between the scaling predictions of the model and the experimental data from de and A-Alamry et al (2011), including both transitions, and with the trend of the experimental data from the present work within regime III, suggest that the model is well-founded. Morrison and Harlen (2010) reported numerical simulations of the jetting of viscoelastic fluids which also showed the same scaling law as that predicted for regime III.…”
Section: B Further Commentssupporting
confidence: 66%
“…However, the observed scaling behavior appears closer to regime II. We note that A-Alamry et al (2011) found that polymer chain scission occurred within the DMP nozzle which would reduce s Z and consequently the value of Wi in the fluid ligament.…”
Section: A Limits For Jetting Of Ps In Depmentioning
confidence: 97%
“…This odd result may be associated with chain scission occurring during either solution preparation or jetting. 45,46 The discrepancy between the results for 1000 kg/mol PEO and the lower molecular weight PEO was slightly more than a factor of 4. Since k eff varies with molecular weight raised to a power of 2.07, chain scission at the chain midpoint may be responsible.…”
Section: A Effects Of Peo Molecular Weight and Concentrationmentioning
confidence: 90%
“…Since k eff varies with molecular weight raised to a power of 2.07, chain scission at the chain midpoint may be responsible. A-Alamry et al 46 have reported evidence of flow-induced polymer degradation during inkjet printing for both poly(methylmethacrylate) and polystyrene in good solvents. Bossard et al 45 studied the rheological properties of PEO (Sigma-Aldrich) solutions as a function of concentration and molecular weight for two dispersion processes: stirring and shaking.…”
Section: A Effects Of Peo Molecular Weight and Concentrationmentioning
confidence: 98%
“…We note that Tirtaatmadja et al [14] suggested using a surface tension reduction agent (2-butanol) to provide a constant equilibrium surface tension for PEO solutions over 10 2 -10 4 ms timescales, but use of such an additive was not considered to be necessary for the shorter timescales accessed by the present experiments. The poly-dispersity index for the PEO samples was unknown but a recent study [15] of the dispersion of high molecular weight PEO in aqueous solution quotes a PDI = 3.33 for PEO from the same supplier, while Tirtaatmadja et al [14] quote PDI ∼ 1.8 for PEO 1 M as a typical value, although the effective PDI may be affected by different methods of PEO solution preparation [15] or even be altered during jetting [16,17].…”
Section: Viscoelastic Fluidsmentioning
confidence: 96%